Compost stream as a potential biomass for humic acid production: Focus on compost seasonal and geographical variability - Negro, Viviana; Montoneri, Enzo; Negre, Michéle; Fabbri, Gloria; Boero, Valter; Solaro, Simone; Antonini, Massimiliano; Koutinas, Apostolis A.; Koutinas, Michalis; Vlysidis, Anestis; Konstantinidis, Viktoras; Mainero, Davide (My University, 2018)
Compost is a voluminous stream rich in humic and fulvic acids, which may be recovered as high-added value compounds. These soluble bio-based lignin-like polymeric substances (SBO) can be extracted through a completely green process developed at pilot scale, whose main core is the hydrolytic route in aqueous solutions at relatively mild temperature (< 140 °C) at ACEA Pinerolese Industriale premises. Due to their chemical-physical properties, the SBO compounds can be used with advantage for myriads of industrial applications, from the formulation of detergents to the production of agriculture biostimulants, answering the increasing demand for bio-compound utilization. In view of LIFECAB project (LIFE16 ENV/IT/000179), the characterization of starting materials and the derived compost has been performed over four seasons and over three European countries (Italy, Greece ad Cyprus). In view of establishing a relationship between SBO molecules and compost properties, this work is a challenging opportunity for assessing the compost variability and its temporal evolution during the composting process. Analyses of pH, salinity, total carbon, total nitrogen and C/N ratio, critically assessed by means of a statistical approach, provide important information about compost composition according to the season and to the local environmental conditions.
Keywords: Bio-stimulants; Compost; Hydrolysis; Humic acids